2021
DOI: 10.3354/dao03562
|View full text |Cite
|
Sign up to set email alerts
|

Competency of common northern sea otter (Enhydra lutris kenyoni) prey items to harbor Streptococcus lutetiensis and S. phocae

Abstract: Streptococcus lutetiensis and S. phocae have been associated with significant morbidity and mortality in northern sea otters Enhydra lutris kenyoni in Alaska, USA, but the route and mechanism(s) of transmission remain unknown. The goal of this study was to determine the competence of common northern sea otter prey to harbor 2 species of pathogenic Streptococcus bacteria. Prey items (bay mussels Mytilus trossulus, butter clams Saxidomus giganteus, Dungeness crab Metacarcinus magister and black turban snails Teg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…mussels) that might accumulate S . phocae and are the prey of several marine mammalian species such as sea otters [ 40 , 41 ]. Further studies are required to identify factors that influence the survival rate of S .…”
Section: Discussionmentioning
confidence: 99%
“…mussels) that might accumulate S . phocae and are the prey of several marine mammalian species such as sea otters [ 40 , 41 ]. Further studies are required to identify factors that influence the survival rate of S .…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between bacterial presence and sand may also be associated with the presence of bivalves. Clams are a preferred sea otter diet item, and experiments have shown that clams can harbor the bacteria (Rouse et al, 2021). Other than in the case of substrate size and bay effect, the results of our logistic regression modeling did not reveal a relationship between SBEC and S .…”
Section: Discussionmentioning
confidence: 99%
“…Published primers targeting a portion of the superoxide dismutase ( sodA ) gene were used to detect S . phocae (Alber et al, 2004) and SBEC (Rouse et al, 2021). Reactions were prepared using 10–12.5 µl of master mix (5Prime Hot Master Mix or OneTaq Hot Start2X), 1 µl forward primer, 1 µl reverse primer, template DNA from bay mussels (500–1000 µg) or positive control bacteria (250–350 µg), and the final reaction volume brought to 25 µl with PCR‐grade water.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations